Mapping the gap: Misalignment between emergency care research and consensus priorities in the Western Cape - Robert Holliman; Colleen J. Saunders (Journal of the Colleges of Medicine of South Africa, 2025)
Background: The Western Cape (WC) province of South Africa is one of the highest emergency care (EC) research-producing regions in Africa. In 2021, a consensus exercise with key stakeholders established 26 EC research priorities. This study aimed to confirm evidence gaps in relation to the priorities and assess the alignment between frontline knowledge needs and research output within the WC EC community.